ANALYSIS OF INCOME INEQUALITY AND ITS IMPLICATIONS ON POVERTY IN SOUTH SUMATRA PROVINCE - Rozali, Muhammad; Hasibuan, Masnilam; Nainggolan, Lora Ekana (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2022)
Indonesia's national economy is experiencing stagnant growth in income inequality (Gini ratio) and the number of poor people continues to increase, even though the national GDP growth indicators have been improving for several years. Regional economic growth in South Sumatra also increased based on the GRDP indicator, but the inequality in income distribution increased slightly and the inflation rate in South Sumatra fluctuated greatly in 2007-2017. Furthermore, the farmer's exchange rate, export value, human development index, and interest rate movements in South Sumatra in 2017 decreased compared to 2007, although overall infrastructure development continues to increase every year. This study analyzes income inequality and its implications for poverty in South Sumatra Province. Factors affecting income inequality are limited to farmers' exchange rates, exports, and infrastructure. The research population is all secondary data related to the research object in South Sumatra Province for the period 2007 - 2017. Based on the Multiple Linear Regression analysis using the OLS (Ordinary Least Square) method, the results show that the exchange rate of farmers' rupiah, exports, and infrastructure simultaneously affects income inequality. Then partially the exchange rate of farmers, exports, and infrastructure have a significant effect on income inequality. The novelty of the research lies in the object of research, where there are differences in the phenomena of economic growth and poverty rates between the National and the Province of South Sumatra.